Cheap Talk? Financial Sanctions and Non-Financial Activity - Tibor Besedeš; Stefan Goldbach; Volker Nitsch (Center for Economic Studies and ifo Institute (CESifo), 2018)
Sanctions restrict cross-border interactions and, therefore, not only put political and economic pressure on the target country, but they also adversely affect the sender country. This paper examines the effect of financial sanctions on the country imposing them. In particular, we analyze the business responses of German non-financial entities to the imposition of sanctions on 23 countries over the period from 1999 through 2014. Examining highly disaggregated, monthly data from the German balance of payments statistics, we find four main results. First, German financial activities with sanctioned countries are sizably reduced after the imposition of sanctions, with strong reductions in the scope of cross-border activities (i.e., the extensive margin) and less robust results for total financial flows which is consistent with the concept of `smart sanctions'. Second, firms doing business with sanctioned countries tend to be disproportionately large, making them largely immune to the reduction in business opportunities with selected partners. Third, firms affected by sanctions expand their activities with non-sanctioned countries, some of which display close trade ties to the sanctioned country. Fourth, we find no effect of sanctions on broader measures of firm performance such as employment or total sales. Overall, we conclude that the economic costs of financial sanctions to the sender country are limited.
Keywords: F20; F36; F38; F51; 330; sanction; restriction; cross-border transaction